A User-Friendly Dashboard for Tracking Global Open Access Performance - Aniek Roelofs; Cameron Neylon; Chun-Kai (Karl) Huang; James Peter Diprose; Kathryn Napier; Katie Wilson; Lucy Montgomery; Rebecca Nina Handcock; Richard Hosking; Richard Rigoni; Tuan-Yow Chien (Journal of Electronic Publishing)
We identify two issues that obstruct the clear assessment of open access publishing performance by academics, librarians, and other stakeholders. Firstly, the current open access categories are difficult to understand and reason about. Secondly, there are no easily accessible tools that allow many countries and institutions to view their open access publishing performance. To address the first issue, we have re-designed the open access categories using descriptive category names rather than opaque colour names, re-organised the categories into a hierarchy to facilitate top-down comprehension, and presented publisher and repository-based open access categories without preferencing one category over the other. To address the second issue, we have developed the COKI Open Access Dashboard, an open-source, public dashboard for measuring and visualising the open access performance of 189 countries and over 7000 institutions. We explore the design decisions underlying the redesigned categories and the dashboard.